Redox-responsive PEGylated self-assembled prodrug-nanoparticles formed by single disulfide bond bridge periplocymarin-vitamin E conjugate for liver cancer chemotherapy - Huiyun Zhang; Wenqian Xu; Emmanuel Omari-Siaw; Yingkun Liu; Baoding Chen; Deyu Chen; Jiangnan Yu; Ximing Xu (Taylor & Francis Group, 2017)
Periplocymarin (PPM), a cardiac glycoside, has a narrow therapeutic index, poor tumor selectivity and severe cardiovascular toxicity which hinder its wide clinical applications in cancer treatment. Herein, we report novel redox-responsive prodrug-nanoparticles (MPSSV-NPs) self-assembled by co-nanoprecipitation of PPM-vitamin E conjugate and a PEG derivative of linoleate (mPEG2000-LA) in water. It was found that the characteristics of PPM-vitamin E nanoparticles (PSSV-NPs) were improved through co-nanoprecipitation with increased percentages of mPEG2000-LA. Moreover, the MPSSV-NPs were optimized according to the in vitro release and cytotoxicity study. Furthermore, the optimized MPSSV-NPs dramatically enhanced the circulation time and tumor distribution of PSSV-NPs after single intravenous injection. The in vivo studies in malignant H22-bearing mice revealed that MPSSV-NPs could effectively suppress tumor growth without causing obvious systemic toxicity. Altogether, these results suggested that MPSSV-NPs could offer a safe, multifunctional and viable nanoplatform for cardiac glycosides in cancer treatment.